2016
DOI: 10.1007/s11846-016-0196-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of innovativeness in SMEs: disentangling core innovation and technology adoption capabilities

Abstract: This paper studies innovativeness in SMEs from a set of innovation indicators at the firm level, capturing various types of innovation (product, process, organisational, and marketing innovations) and the level of innovativeness in these firm's developments. The article identifies two separate dimensions in the innovativeness of Spanish SMEs, using factor analysis techniques. One dimension is associated with the capabilities for core/internal innovation and the other with the capabilities for the adoption of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 116 publications
5
52
0
1
Order By: Relevance
“…The second organizational factor we analyze refers to investment in innovation. The literature shows that firms develop inter‐firm agreements to become more innovative and enhance the outcomes of R&D investments (Baum, Calabrese, and Silverman ; Martínez‐Román and Romero ; Powell, Koput, and Smith‐Doerr ). Through cooperation, firms can access knowledge and technologies, share resources, and accelerate the innovation process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second organizational factor we analyze refers to investment in innovation. The literature shows that firms develop inter‐firm agreements to become more innovative and enhance the outcomes of R&D investments (Baum, Calabrese, and Silverman ; Martínez‐Román and Romero ; Powell, Koput, and Smith‐Doerr ). Through cooperation, firms can access knowledge and technologies, share resources, and accelerate the innovation process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The external environment plays an important role in the functioning of enterprises (Furman et al, 2002;Özsomer et al, 1997;Ramanathan et al, 2018), including small and medium-sized enterprises (Martinez-Roman and Romero, 2017;Romero and Martinez-Roman, 2012;Yam et al, 2011). It is a source of both opportunities and threats to their current and future activities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The most commonly used include the size of the enterprise (Guan and Ma, 2003;Hurley and Hult, 1998;Martinez-Roman et al, 2011). Other relevant contextual factors include the industry or sector of operation, and the type of market (domestic or foreign) (Alves et al, 2017;Liu et al, 2017;Martinez-Roman and Romero, 2017;Yam et al, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Scholars firstly pay attention to the impact of Universities on innovation. Juan [35] and Broekel [36] found that higher education also plays an important role in the process of innovation, and universities and innovation ability have an obvious direct or indirect correlation. Hojin [37] studies the impact of Technological Exploration on industrial technology development from the perspective of demand.…”
Section: Analysis Of Ltimentioning
confidence: 99%